Pengemasan Materi Ajar Tari Gobuk melalui Aplikasi Youtube untuk Siswa Sekolah Menengah Atas - Putri, Didra Amira; Heniwaty, Yusnizar (Universitas Negeri Medan, 2025)
This study aims to describe the steps of Gobuk Dance packaging as teaching material through the Youtube application to display uploads containing Gobuk Dance in accordance with the Merdeka Curriculum, Phase E Learning Outcomes, namely: